Evolution of Maintenance Systems of Passenger and Freight Wagons from the ECM Certification Point of View - Peter Zvolensky; Vladimir Stuchly; Juraj Grencik; Roman Poprocky (Communications - Scientific letters of the University of Zilina, 2014)
RCM and ECM are abbreviations seemingly the same though the meaning is different. However, they have lot of common as the both are aimed at increased reliability of operation and minimising risk. RCM stands for Reliability Centred Maintenance and ECM stands for Entity in Charge of Maintenance, thus maintenance is the common term for both. Indeed, maintenance is a key for increased safety and reduced risk. The paper presents basic principles and theory behind the RCM – an advanced maintenance concept with its origin in aviation and consequently applied in industries connected with high level of risk, such power generation, etc. The ECM certification is a new approach for assessment of how railway vehicles operators are managing the risks connected with operation of the rolling stock. Entities, either owners or keepers of the rolling stock, are those who are responsible for the technical condition guaranteeing safety of railway traffic. There is common European methodology (requirements) for assessing the competence of ECMs based on EC Regulation No. 445/2011. Behind this methodology are efforts to minimise risks of freight trains operation and prevent serious accidents resulting from improper maintenance and insufficient technical state. In line with these efforts is our proposal for implementation of RCM in railway vehicles maintenance.